Analysis of technologies for recycling the waste generated in concrete production in ready mixed concrete plants. - Vieira, Luiz de Brito Prado (2020)
The large volume of waste generated in construction is a relevant problem from a financial and environmental point of view. Therefore, a waste elimination strategy in the production of concrete is of great importance. This thesis aims to propose a method of evaluating the efficiency of strategies to minimize residues generated in the ready-mix concrete (RMC) production through laboratory and industrial tests. The experimental study was initiated by the production of an inventory on the volumes of waste generated in the production of RMC under real operating conditions. The causes and the amount of waste generated by the concrete company were analysed. The study took place over a period of one year and involved 94 RMC plants. The inventory was produced under real operational conditions and measured the influence of concrete characteristics on the volume of concrete adhered to the mixer truck drum. The experimental study was performed and measured the influence of concrete characteristics. The causes of returned concrete were also evaluated. It was found that the total volume of waste produced in the concrete corresponds to 3.1% of the total volume produced. In addition, 45% of the waste produced corresponds to leftovers, the main cause of which is excessive ordering (57.9%). Adhered concrete corresponds to 55% of the total volume of waste generated, with the low level of concrete slump being the main factor causing the increase in this volume. The three main waste reduction strategies used by concrete companies were evaluated for the technical, financial feasibility and CO2 emissions of each of the studied strategies. The methodology used employed laboratory evaluation followed by monitoring and parameterization of production on an industrial scale. The results obtained allowed to determine the real capacity of these techniques to reduce the waste and the specific CO2 footprint of the RMC. Three different methods of reusing residues were analysed: (a) reusing fresh concrete using hydration stabilizing additives (HSA); (b) reuse of fresh concrete by separating the aggregates from the cement paste before the concrete hardens; (c) recycling of hardened concrete through the production of crushed recycled aggregates. The method of concrete reuse with HSA has clear advantages in relation to the others analysed from the environmental and financial point of view, making this very attractive strategy for implementation in RMC plants. From a technical point of view, this strategy has the advantage of simultaneously allowing the reuse of the returned concrete and the adhered concrete. On the other hand, the use of HSA demands a greater investment from an operational point of view and, in particular, of training of labour. Therefore, the analysis methodology combining laboratory results and monitoring of production conditions proved to be effective in analysing strategies for mitigating waste production in concrete companies.